A NEW APPROACH TO ANALYSE LENGTH AND QUALITY OF RICE USING FLATBED SCANNER - Usha , Swarnala; T. , Devi; N., Deepa (International Journal of Psychosocial Rehabilitation, 2020)
Rice is one of the major things that a human being comes across in day-to-day life, and rice is one of the most favourable food items and most consuming food items for human beings. Measuring the quality of the rice is also important because it is mostly consumed by human beings. India is one of the countries like China and Japan that produce rice, and rice is one of the major food items in India, especially in the southern part. Many researchers have been done on the improvement of the quality of the rice; today we are going to focus on one of the most efficient ways to measure the quality of the rice. There are many researchers who have been done on measuring the quality of the rice with different algorithms. In this paper we are going to predict the quality of the rice by measuring the edges of the rice. In this paper, we perform the experiment on different rice grains and check the quality of the rice grains by finding the edges of the rice grain.